Analysis of Vitamin K1 in Soybean Seed: Assessing Levels in a Lineage Representing Over 35 Years of Breeding. (25th February 2016) - Thompson, Melissa M.; Niemuth, Ashley; Sabbatini, Jane; Levin, David; Breeze, Matthew L.; Li, Xin; Perez, Timothy; Taylor, Mary; Harrigan, George G.
Abstract: Recommendations by the Organization of Economic Cooperation and Development (OECD) for compositional assessments of new genetically modified (GM) soybean now include measurement of vitamin K1 . Here we employ an HPLC method to provide information on variation in levels of vitamin K1 in seed from soybean representing over 35 years of breeding. Vitamin K1 analysis was conducted on seed from six conventional lines and three GM glyphosate‐tolerant lines grown concurrently at two sites in the US. Vitamin K1 levels in seed were influenced by both location and germplasm. Levels were higher in the newer higher‐yielding lines when compared with the older varieties. The effect of GM was negligible. Overall, our study showed, using a method suitable for compositional assessments under OECD guidelines, that (i) variation in levels of vitamin K1 in soybean is associated with a safe history of consumption and (ii) that modern breeding strategies can be employed for soybean varietal development without adversely impacting vitamin K1 levels.